(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2016)
Climate change is negatively affecting livelihoods dependent on rain fed agriculture in Kenya. Adaptation through adoption of appropriate agricultural technologies is necessary. Communication plays a critical role in dissemination of climate change information and adaptation. The study applied social network analysis (SNA) using NodeXL computer programme to generate socio-grams that showed patterns of information flow from which important network and individual characteristic of the opinion leaders were described. This study shows that SNA is applicable in climate change communication to identify opinion leaders by mapping out information flow patterns and using measures of centrality. Int. J. Agril. Res. Innov. & Tech. 6 (1): 1-7, June, 2016